Desaturases: Emerging Models for Understanding Functional Diversification of Diiron-containing Enzymes - Shanklin, John (American Society for Biochemistry and Molecular Biology, 2009)
Desaturases and related enzymes perform O(2)-dependent dehydrogenations initiated at unactivated C-H groups with the use of a diiron active site. Determination of the long-sought oxidized desaturase crystal structure facilitated structural comparison of the active sites of disparate diiron enzymes. Experiments on the castor desaturase are discussed that provide experimental support for a hypothesized ancestral oxidase enzyme in the context of the evolution of the diiron enzyme diverse functionality. We also summarize recent analysis of a castor mutant desaturase that provides valuable insights into the relationship of proposed substrate-binding modes with respect to a range of catalytic outcomes.